Silicon electronics on silk as a path to bioresorbable, implantable devices - Kim, Dae-Hyeong (American Institute of Physics, 2009)
Many existing and envisioned classes of implantable biomedical devices require high performance electronics∕sensors. An approach that avoids some of the longer term challenges in biocompatibility involves a construction in which some parts or all of the system resorbs in the body over time. This paper describes strategies for integrating single crystalline silicon electronics, where the silicon is in the form of nanomembranes, onto water soluble and biocompatible silk substrates. Electrical, bending, water dissolution, and animal toxicity studies suggest that this approach might provide many opportunities for future biomedical devices and clinical applications.